[2-(2-Chlorophenyl)-2-hydroxyethyl](isopropyl)ammonium 4-hydroxybenzoate - Zhou, Ling (International Union of Crystallography, 2010)
The title molecular salt, C(11)H(17)ClNO(+)·C(7)H(5)O(3) (−), was obtained by the reaction of racemic clorprenaline and 4-hydroxybenzoic acid. In the crystal, the components are connected by O—H⋯O and N—H⋯O hydrogen bonds, resulting in a two-dimensional hydrogen-bonded network.